A new anisotropic adaptive mesh photochemical model for ozone formation in power plant plumes. (15th May 2020) - Zheng, J.; Fang, F.; Wang, Z.; Zhu, J.; Li, J.; Li, J.; Xiao, H.; Pain, C.C.
Abstract: In this work, an advanced dynamically adaptive unstructured mesh technique is introduced to photochemical modeling, which provides a consistent way to resolve the complex chemical transport processes over a wide range of spatial scales from meters (near point sources) up to hundred kilometers without the Gaussian distribution assumption (often used in existing subgrid Plume-in-Grid (PinG) models, such as RPM and SCICHEM). To assess the performance of the new photochemical model, the numerical results (NO x and O 3 ) have been compared to the Southern Oxidants Study (SOS) 1999 aircraft plume measurements, where the range of the emission intensity is from 1.8 to 13.9 ton/h. The relative error in the peak value of NO x and O 3 is between 10%–20% within 66 km downwind distance. The results show that the use of dynamically adaptive meshes can reproduce the details of the plume chemistry evolution: the slender puff structure of high NO x concentrations within a few kilometers width near the point sources, and the wing-like structure of ozone concentration during the plume growth, which is hard to capture for the PinG models or photochemical grid models. Highlights: A single unified integrated photochemical model (Fluidity-Chem). Introduction of advanced anisotropic dynamic meshes to photochemical modeling. Improved accuracy by resolving the details of chemical and transport processes. A good agreement between numerical results and aircraft plume measurements.